Eliminating mother-to-child transmission of HIV in Tanzania calls for efforts to address factors associated with a low confirmatory test. - Baraka M Morris; Mukome Nyamhagata; Edith Tarimo; Bruno Sunguya (Public Library of Science (PLoS), 2023)
Option B+ approach for prevention of mother-to-child transmission (PMTCT) has demonstrated the potential to eliminate pediatric HIV infections. Its success depends on early infant diagnosis (EID) of HIV among the exposed infants within the first 6 weeks, and a subsequent confirmatory HIV test within 18 months. However, most mothers enrolling in option B+ in Tanzania do not come for such confirmatory tests. We examined factors associated with the turning-up of mother-baby pairs on the PMTCT program for a confirmatory HIV testing 18 months post-delivery in Tanzania. This study utilized longitudinal data collected between 2015 and 2017, from 751 mother-baby pairs enrolled in the PMTCT-option B+ approach in 79 health facilities from the 12 regions of Tanzania-mainland. Only 44.2% of 751 mother-baby records observed received the HIV confirmatory test by the 18th month. Mothers aged 25 years or above (adults' mothers) were 1.44 more likely to turn up for confirmatory HIV testing than young mothers; mothers with partners tested for HIV were 1.74 more likely to have confirmatory HIV testing compared with partners not tested for HIV. Newly diagnosed HIV-positive mothers were 28% less likely to bring their babies for a confirmatory HIV-testing compared to known HIV-positive mothers. Mothers with treatment supporters were 1.58 more likely to receive confirmatory HIV-testing compared to mothers without one. Mother-baby pairs who collected DBS-PCR-1 were 3.61 more likely to have confirmatory HIV-testing than those who didn't collect DBS-PCR-1. In conclusion, the confirmatory HIV testing within 18 months among mother-baby pairs enrolled in the Option B+ approach is still low in Tanzania. This is associated with low maternal age, having a male partner not tested for HIV, lack of experience with HIV services, lack of treatment supporters, and failure to take the DBS-PCR-1 HIV test within the first two months post-delivery.